2013
DOI: 10.1111/nmo.12114
|View full text |Cite
|
Sign up to set email alerts
|

Myenteric neuron numbers are maintained in aging mouse distal colon

Abstract: BACKGROUND Age-associated myenteric neuronal loss has been described in several species. In some studies,cholinergic neurons have been reported to be selectively vulnerable, whereas nitrergic neurons are spared. Aging of the mouse enteric nervous system(ENS) and the subtypes of mouse myenteric neurons that may be lost have been little studied. We therefore investigated changes in the numbers of total neurons and two neuronal subpopulations in the mouse distal colon during aging. METHODS Wholemount preparations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 31 publications
5
60
2
1
Order By: Relevance
“…These results support those from other studies,which have also shown that NK 2 blockade can reduce the amplitude of colonic migrating motor complexes (CMMCs), a motility pattern believed to contribute to fecal pellet propulsion (Brierley et al, 2001). The precise causes ofthe decrease in NK 2 -mediated signaling are unclear and may possibly reflect the loss of myenteric neurones,whichhas been recorded in many species including humans (Saffrey, 2013).However, we have recently shown that myenteric neuronal numbers do not decrease with age in the distal colon of the C57BL/6J male mice suggesting that the changes observed reflect the altered functioning of a fixed neuronal pool (Gamage et al, 2013). It has been suggested that the lack of change in neuronal number in thatstudyis species-specific or reflects subtle changes in the strain of mouse used or the diet that the animals have been maintained on (Kapur, 2013;Saffrey, 2013).…”
Section: Accepted M Manuscriptmentioning
confidence: 89%
“…These results support those from other studies,which have also shown that NK 2 blockade can reduce the amplitude of colonic migrating motor complexes (CMMCs), a motility pattern believed to contribute to fecal pellet propulsion (Brierley et al, 2001). The precise causes ofthe decrease in NK 2 -mediated signaling are unclear and may possibly reflect the loss of myenteric neurones,whichhas been recorded in many species including humans (Saffrey, 2013).However, we have recently shown that myenteric neuronal numbers do not decrease with age in the distal colon of the C57BL/6J male mice suggesting that the changes observed reflect the altered functioning of a fixed neuronal pool (Gamage et al, 2013). It has been suggested that the lack of change in neuronal number in thatstudyis species-specific or reflects subtle changes in the strain of mouse used or the diet that the animals have been maintained on (Kapur, 2013;Saffrey, 2013).…”
Section: Accepted M Manuscriptmentioning
confidence: 89%
“…14 In the present study, in the AC and DC, neuronal areas as indicated with PGP 9.5-immunoreactive areas increased in adolescence, and decreased to the level of young rats in old age; the loss of myenteric neurons with age was consistent with previous reports in aged mice and rats. 51,52 In addition, nNOS expression visible on Western blotting decreased according to age. However, there was a slight increase in 2-year old rats compared to 74-week old rats.…”
Section: Discussionmentioning
confidence: 99%
“…24 In mice, myenteric neurons were maintained in aging DC. 51 In rats, there were no losses of nitrergic neurons stained with nicotinamide adenine dinucleotide phosphate diaphorase (NADPHd) in the stomach, small intestine, or large intestine. 25 However, the total population of neurons stained with Cuprolinic Blue was reduced in both the aged small intestine and large intestine.…”
Section: Discussionmentioning
confidence: 99%
“…These studies were carried out in a number of animal species [27,29,31]. The literature that has been documented support varying data from those which indicate the significant reduction (30-50%) in the number of neurons [17,33] to those where there is no significant loss of the neurons [14,24,36] in the aging process. There are a number of studies [7,34] which describe changes in ENS due to the introduction of certain dietary restrictions in experimental animals.…”
Section: Introductionmentioning
confidence: 99%